REBELLIONS, REVOLTS, CONSPIRACIES, UNRESTS AND PROTESTS IN SERBIA FROM 1815 TO 2006 - Matić, Goran (Political Review, 2025)
Rebellions, revolts, uprisings, and also citizen protests and riots are often signs of deep division and crisis in society and may bring about significant political changes, as well as long-lasting conflicts and instability. When we observe the political scene in Serbia from the inception of the modern statehood in 1815 to the disintegration of the State Union in 2006, we can state that it was pervaded by rebellions, protests, liberation wars, and world wars, changes in the system of government and political systems, which had inescapably left consequences on both Serbian thought and science. Finally, we can conclude that rebellions, revolts, conspiracies, riots, and protests that happened in the course of the 19th century left both positive and negative marks on the national identity of Serbs, especially on the culture, political theory, as well as on the constitutional and criminal law.
Keywords: politics; security; history; political violence; revolt; conspiracy